2021
DOI: 10.3390/antibiotics10091132
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Nanoformulation for Biocontrol of Tomato Root and Crown Rot Caused by Fusarium oxysporum f. sp. radicis-lycopersici

Abstract: Tomatoes (Solanum lycopersicum L.) are the most cultivated and important vegetable crop in the world. These plants can wilt during crop growth due to fusarium wilt (fusariosis), a disease that damages tomato vascular systems. The Fusarium isolated and analyzed in this work correspond to Fusarium oxysporum f. sp. radicis-lycopersici. The isolates were molecularly identified, and analysis was done on the in vitro effects of the nanoemulsions (previously obtained from extracts of Chilean medicinal plants of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Further, Saltos-Rezabala et al [64] tested the efficiency of thyme EO in reducing the severity of early blight of tomato and found that the infected leaf area and final disease index were reduced by 47.8% and 39%, respectively. Plant extracts have great potential given their diverse origins and abilities to inhibit the mycelium growth, spore germination, and control over viability of conidia [65]. Our investigation revealed that all methanol plant extracts showed strong activity against the mycelium growth of pathogenic fungi, except for O. basilicum at a 5% concentration.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Further, Saltos-Rezabala et al [64] tested the efficiency of thyme EO in reducing the severity of early blight of tomato and found that the infected leaf area and final disease index were reduced by 47.8% and 39%, respectively. Plant extracts have great potential given their diverse origins and abilities to inhibit the mycelium growth, spore germination, and control over viability of conidia [65]. Our investigation revealed that all methanol plant extracts showed strong activity against the mycelium growth of pathogenic fungi, except for O. basilicum at a 5% concentration.…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have confirmed the efficiency of PEs in reducing the incidence of fungal diseases by performing directly or indirectly by inhibiting the growth and reproduction of fungi [65]. PEs have been shown to inhibit of pathogenic fungi through three modes of action: increasing fungal mortality (fungicidal effect), inhibiting fungal growth and development (fungistatic effect), and/or improving plant growth by inducing the defense responses of infected plants [36].…”
Section: Discussionmentioning
confidence: 99%
“…lycopersici , which moves through the xylem, F. oxysporum f. sp. radicis-lycopersici begins colonisation in areas where the root grows and moves towards the crown of the root, where it blocks the vessels by producing enzymes and toxins [ 33 ]. This leads to the wilting and death of the plants.…”
Section: Tomato Diseases and Pathogensmentioning
confidence: 99%
“…Graphene and its derivatives are extensively used in different industries, including electronics [ 13 ], energy storage and conversion [ 14 ], optics [ 15 ], and most recently, bioscience and biotechnology [ 16 ]. Due to their large surface area and outstanding thermal and electrical conductivity, they were employed in the creation of bio- and immune-sensors [ 17 ], DNA sensing [ 18 ], biocomposites [ 19 ], gene delivery [ 20 ], pathogen sensing at the single-cell level [ 21 ], tissue engineering [ 22 ], and antifungal properties [ 23 ].…”
Section: Introductionmentioning
confidence: 99%